Pelestarian Situs Kepurbakalaan Candi Muara Jambi di Kecamatan Muaro Sebo Kabupaten Muaro Jambi - Yusdi Anra; Amir Syarifuddin (Universitas Batanghari Jambi, 2019)
The purpose of this research was to find out how far the society of Muaro Sebo district in Muaro Jambi Regency understands the preservation and conservation of Muaro Jambi temple complex. This research was qualitative research. The research was conducted in Muaro Sebo district, Muaro Jambi Regency, Jambi Province. The informants in this research were: 1) Indigenous Village Leaders of Muaro Sebo Village, 2) Management Group of Muaro Jambi Temple Complex, 3) Employees in the Department of Tourism Heritage, Jambi Province. 4) Non-Governmental Organizations, and 5) Muaro Sebo society of Muaro Jambi Regency. Data were collected by using interview, observation, and documentation studies. Data analysis techniques in this research were data reduction, data display / data presentation, conclusions and then verified. Based on the research findings and discussion, it can be concluded as follows. First, Performance of Cultural Heritage Conservation Management Group Muaro Jambi temple Complex has been arranged in the form of legal recognition by the Muaro Jambi District Government. Second, the utilization of Muaro Jambi temple complex as a superior tourism object that must be maintained and cared for by all people, especially, Muaro Sebo District society of Muaro Jambi Regency, with performance and local wisdom one form of values, attitudes, perceptions, behaviors and responses of the local community that interacts with a system of life with nature and the environment. Third, the obstacles in managing the utilization of this temple complex were very little awareness of the surrounding society to maintain and care to this temple sites. So, it takes hard work to continue and to increase awareness of the surrounding society to guard this temple site. Fourth, need active role of academics to assist in providing understanding, so that the Muaro Jambi enshrinement sites are getting better organized.